THE EFFECT OF OUTLINE PLANNING IN ARGUMENTATIVE ESSAY WRITING OF FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT, FACULTY OF ARTS, UDAYANA UNIVERSITY - Indriani, Ketut Santi (Lingual Journal of Language and Culture; Vol 8 No 2 (2019): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2019.v08.i02.p02, 2020)
This study is aimed to identify the effect of outline planning in argumentative essay writing of fourth semester students of English Department, Faculty of Arts, Udayana University.  Outlining is making a plan to map your writing which shows the content and the sequence of each paragraph in your writing. Task planning will give the students an opportunity to plan what to say and how to write their ideas in the task performance. Task planning can be in the form of cubing, clustering, mapping (Ojima, 2006:566), and outlining (Kellog, 1990: 328). The data source of this study are argumentative essay writing of 30 students. The data in this study was analysed both qualitatively and quantitatively. The data analysis was done by comparing the results of the pre-test and post-test in argumentative essays writing. Pre-test was conducted without outlining the writing while post-test proceeded by outlining the writing. Based on the data analysis, the results shows that there is a significant improvement in students writing after the implementation of the outline planning. The improvement reflected from the reduction of the types and the number of mistake made by the students in their writing.